The effect of publicly provided health insurance on academic performance in Mexico - Carlo Alcaraz; Daniel Chiquiar; María José Orraca; Alejandrina Salcedo (Banco de México, 2012)
In this paper we study the causal effect of a large expansion of publicly provided health insurance on children's academic performance using the case of Mexico. In general, access to free health insurance could improve education outcomes directly by making household members healthier or indirectly by raising the amount of resources available for education expenses. Using a panel of municipalities from 2007 to 2009, we find that the expansion of the Mexican public health insurance program, Seguro Popular, had a positive, statistically significant effect on standardized test scores of primary school children.
Keywords: I13; I15; I25; I38; 330; Health insurance; Public health; Seguro Popular; Mexico; Education; Test scores; Gesetzliche Krankenversicherung; Bildungsverhalten; Schüler; Mexiko